Finite element analysis of clear aligner with overhanging attachments and extended gingival coverage for interdental space closure - Zeng, Guojin; Ma, Xiaoqing; Lin, Dan (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveOverhanging (OH) attachments were modified clear aligner (CA) attachments with an extended portion toward the root to apply force closer to the center of resistance and enable greater control over root movement, resembling power arms. This study investigated the biomechanical effects of OH attachment and partially gingival extension of CA trimline on canine movement during the closure of extraction space via finite element analysis (FEA).MethodsCBCT data of an adult with Angle Class I molar relationship and mild anterior crowding was applied for comparing the biomechanical effects of three attachment types (no attachment, vertical, OH) and four trimline designs (partially buccal/lingual gingival coverage). Periodontal ligament (PDL) hydrostatic stress, tooth displacement, rotational center position, and CA stress distribution were assessed via FEA.ResultsOH attachment induced increased tooth displacement and PDL hydrostatic stress (95.5 kPa) compared to regular vertical attachment (53.1 kPa) in achieving root-controlled canine movement. OH attachment combined with a buccolingual gingival extension of CA trimline on 2–6 facilitated the most translational canine movement and lowest ratio of mesio-apical to disto-occlusal displacement (0.466, compared to 0.506 in group with no attachment and trimline extension), while simultaneously avoiding excessive aligner deformation and stress concentration.ConclusionOverhanging attachment combined with partial gingival extension of CA trimline significantly enhanced the orthodontic force for premolar extraction cases involving space closure between canines and molars, as a more efficient and feasible design for canine bodily movement.